Autonomous tennis ball retriever - Chew, Clement Wen Hao. (2008)
The Autonomous Tennis Ball Retriever project was selected because the project budget is reasonable, product goals or objectives are achievable., it represents the invention of a smart product; and the author’s personal interest in the game of tennis acts as a motivation factor.